2017
DOI: 10.7566/jpsj.86.104703
|View full text |Cite
|
Sign up to set email alerts
|

Negative Refraction in Weyl Semimetals

Abstract: We theoretically propose that Weyl semimetals may exhibit negative refraction at some frequencies close to the plasmon frequency, allowing transverse magnetic (TM) electromagnetic waves with frequencies smaller than the plasmon frequency to propagate in the Weyl semimetals. The idea is justified by the calculation of reflection spectra, in which negative refractive index at such frequencies gives physically correct spectra. In this case, a TM electromagnetic wave incident to the surface of the Weyl semimetal w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…A number of recent studies have suggested that Weyl semimetals (WSMs) should have highly unusual optical response originated from unique topological properties of their bulk and surface electron states; see e.g. [1][2][3][4][5][6][7][8][9][10][11][12][13] and references therein. Their optical response can be used to provide detailed spectroscopic information about their electronic structure which could be difficult to obtain by any other means.…”
mentioning
confidence: 99%
“…A number of recent studies have suggested that Weyl semimetals (WSMs) should have highly unusual optical response originated from unique topological properties of their bulk and surface electron states; see e.g. [1][2][3][4][5][6][7][8][9][10][11][12][13] and references therein. Their optical response can be used to provide detailed spectroscopic information about their electronic structure which could be difficult to obtain by any other means.…”
mentioning
confidence: 99%
“…Note added: After completion of this work, we found a similar work discussing the negative refraction in Weyl semimetals based on anomalous Hall effect [23]. Our proposal might be robust compared to Ref.…”
mentioning
confidence: 64%
“…Our proposal might be robust compared to Ref. [23], since it does not rely on microscopic structures of Weyl nodes, and can be applied to both of Weyl and Dirac semimetals.…”
mentioning
confidence: 99%
“…Recently, ideal Weyl nodes was achieved in artificial photonic crystal structures [10]. WSM has attracted much attention due to its many exotic properties induced by the Weyl nodes, such as anomalous Hall effect [1,11], surface states with Fermi arcs [12,13], peculiar electromagnetic response [14,15], and negatice magneto-resistivity [16][17][18][19]. A WSM can be proved by observing its Fermi arcs with separated Weyl nodes.…”
Section: Introductionmentioning
confidence: 99%